GROWTH, YIELD, HEAVY METALS AND MICROORGANISMS IN SOIL AND FRUIT OF PECANS FERTILIZED WITH BIOSOLIDS - Tarango-Rivero, Socorro Héctor; Alarcón-Herrera, María Teresa; Orrantia-Borunda, Erasmo (Revista Mexicana de Ciencias Agrícolas, 2018)
The application of anaerobically digested biosolids as a nutrient source for the pecan Carya illinoinensis (Wangeh.) K. Koch, cultivar Western, during three years was evaluated. The bearing shoot grew 16% more and nut production per tree was 11.3% higher in the biosolid treatment, on a three-year average. The accumulation of As, Cd, Cr, Hg, Ni and Pb in soil due to biosolids was very low and according to the U.S. standard, the maximum allowable concentration would be reached in 34 years. Quantities of Cd, Cr, Ni and Pb in the kernel were below detection limits. As and Hg were found in very small quantities, and were below the limits allowed for nuts in the United Kingdom. During the preharvest, in soil fertilized with biosolids and in nuts which had contact with biosolids, the presence of Escherichia coli and Salmonella sp. were not detected.
Keywords: Carya illinoinensis; Escherichia coli; Salmonella sp.; heavy metals